Gender of Children, Bargaining Power, and Intrahousehold Resource Allocation in China - *Li, Lixing; Wu, Xiaoyu (Journal of Human Resources, 2011)
Based on the prevalent son preference in China, this paper proposes a new measure of relative bargaining power within the household. Using data from China Health and Nutrition Survey, we show that a woman with a first-born son has a 3.9 percentage points' greater role in household decision-making than a woman with a first-born daughter Having a first-horn son improves the mother's nutrition intakes and reduces her likelihood of being underweight. While thinking of these impacts as being channeled through intrahousehold bargaining power we cannot fully rule out other possible direct effects of a first-born son on the outcomes.